Unique role of CD4(+)CD62L(+) regulatory T cells in the control of autoimmune diabetes in T cell receptor transgenic mice - You, Sylvaine (National Academy of Sciences, 2004)
Converging experimental evidence indicates that CD4(+) regulatory T cells control progression of autoimmune insulitis in nonobese diabetic (NOD) mice. Here, we studied the nature of these regulatory T cells and their mode of action in diabetes-prone NOD Rag(-/-) or severe combined immunodeficient (SCID) mice harboring a transgenic T cell receptor derived from the diabetogenic T cell clone BDC2.5. We first show that diabetes onset is prevented in such mice by infusion of polyclonal CD4(+) T cells expressing l-selectin (CD62L) but not prevented or only marginally prevented by CD4(+)CD25(+) T cells. Similarly, we found with a cotransfer model that CD4(+)CD62L(+) T cells but not CD4(+)CD25(+) T cells inhibited diabetes transfer into NOD SCID recipients by transgenic NOD BDC2.5 SCID cells. Unexpectedly, cotransfer of transgenic NOD BDC2.5 SCID cells and spleen cells from WT diabetic NOD mice did not induce diabetes, whereas each individual population did so. Data are presented arguing for the role of CD4(+)CD62L(+) T cells present within the polyclonal diabetogenic population in mediating this apparently paradoxical effect. Collectively, these data confirm the central role of CD4(+)CD62L(+) regulatory T cells in controlling disease onset in a well defined transgenic model of autoimmune diabetes and suggest the intervention of homeostatic mechanisms as part of their mode of action.